VALUE RELEVANCE OF EPS AND BVPS: THE MODERATING ROLE OF PSAK 71 - Haidar Faqih Fadhilah; Imam Abu Hanifah; Iis Ismawati (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: Prior IFRS 9/PSAK 71 value-relevance research is concentrated in banking and does not explain whether expected-credit-loss information changes how investors interpret earnings and book value in non-financial, asset-intensive firms. This study examines the value relevance of earnings per share (EPS) and book value per share (BVPS) and tests whether Cadangan Kerugian Penurunan Nilai (CKPN), the recognized impairment allowance under PSAK 71, moderates their associations with share prices. Research Methodology: A quantitative explanatory-associative design was applied to 38 basic materials companies continuously listed on the Indonesia Stock Exchange during 2016–2024, yielding 342 balanced firm-year observations. Moderated panel regression was estimated with firm and year fixed effects and White cross-section robust standard errors in EViews. Results: EPS is positively associated with share price, whereas the direct BVPS coefficient is negative. CKPN does not significantly moderate the EPS–price association, but the BVPS × CKPN interaction is positive and significant. At the sample mean of CKPN, the estimated marginal BVPS coefficient is slightly positive. The model has an adjusted R-squared of 0.484. Conclusions: Earnings remain a primary performance signal, while the market relevance of book value is conditional on information about asset quality and expected credit risk. The evidence indicates that PSAK 71 produces an asymmetric valuation effect rather than uniformly changing all accounting signals. Limitations: The study covers one non-financial sector, uses one observable PSAK 71 proxy, and cannot fully eliminate time-varying omitted variables or reverse causality. Contributions: The study extends value-relevance evidence beyond banking by integrating residual-income valuation, signaling, agency, and resource-orchestration perspectives. It shows that CKPN simultaneously conveys adverse credit-risk information and improves the credibility of net assets. Managers should therefore treat ECL estimation, receivables governance, and related disclosure as strategic asset-quality practices, while investors should evaluate BVPS jointly with impairment information.